Clinico-Epidemiological Profile of COVID-19 of Patients Presenting to Emergency Department of a Tertiary Medical College of Central Nepal - Pradhan, Alok; Pradhan, Manohar; Kayastha, Bhagirathi (Journal of College of Medical Sciences-Nepal, 2024)
Background Clinico-epidemiological profile of COVID-19 includes varied clinical symptoms like fever, cough, and fatigue, with a potential for rapid community spread through respiratory droplets. Understanding the clinical characteristics of patients is crucial for planning human resources and logistics support. This study aims to identify the clinical characteristics observed in patients suspected of having COVID-19 presenting to emergency department of College of Medical Sciences and Teaching Hospital. Methods This is a retrospective cross-sectional study conducted at Department of General Practice and Emergency Medicine of College of Medical Sciences, Bharatpur, Nepal from April 2020 to February 2021. Ethical approval was taken from institutional review committee of College of Medical Sciences. Data was collected from record file of emergency department. Data was entered and analyzed by using descriptive statistical tools in SPSS-20. Results Majority (25.2%) of them were in the age group 50-60 years. Mean±SD of age was 55.2±16.5 years. Majority (54.3%) respondents were male. In presenting complaints 71.42% had cough, 69.5% had fever, 62.9% had shortness of breath. Also, 34.28% had severe symptoms, and 33.34% had moderate symptoms, 20% were asymptomatic and 12.38% had mild symptoms. Finding showed that 69.52% of patients required oxygen supplementation. The motility of COVID-19 patients during emergency stay was 6.67% while 36.19% were admitted in ward and 31.43% were admitted in ICU, 20% patients were sent for home isolation. Conclusions Young adults were the most commonly affected age group and males showed a higher incidence of COVID-19. Since many patients were symptomatic with fever and cough as the typical presentations in the emergency department. Majority of patients during presentation had moderate and severe symptoms and needed oxygen supplementation.